Implementation of Green Tax in Malaysia: An Exploratory Study - Saad, Natrah; Ariffin, Zaimah Zainol (Growth, 2019)
This study provides empirical evidence on the perception of green tax mechanisms that are currently implemented in Malaysia. This study is undertaken in response to increasing incidents of environmental degradation taking place in our country as a result of business activities. In particular, this study sets to explore the current practice of green tax in Malaysia and its effectiveness in achieving the intended goal of green environment. For that purpose, a qualitative approach of data collection was conducted, mainly through interviews and document review. Hence, 11 participants representing government agencies and industries were interviewed and data gathered were transcribed and analysed accordingly using thematic analysis. Annual reports and performance reports were also reviewed to complement the findings. Among others, the findings indicate that green tax practice in Malaysia is merely focused on incentive-based which are under jurisdiction of Malaysian Investment Development Authority and the Inland Revenue Board Malaysia (IRBM). The authority to impose penalties (which are not related to tax) rests with the Department of Environment. The practice is slightly different from the developed country which blends both incentive-based and penalty-based under jurisdiction of the tax authority. It is hoped that these findings would assist the relevant agencies to formulate the strategies in their effort to preserve our natural heritage.